PENGGUNAAN BULLETIN BOARD DAN HASIL BELAJAR SISWA - Heslin Bine' Rumambo (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The bulletin board is one of the static visual learning media that can be placed anywhere inside the classroom, characterized as open, so it can be read and observed at any time. By using descriptive quantitative research and chi-square testing, namely the test of independence (Contingency Table Analysis), the aim is to observe and determine the extent of the relationship between the use of bulletin board learning media and the improvement of students' learning outcomes, especially after conducting presentations. The research target is the students of SMP Kristen Kandora, Mengkendek District, Tana Toraja Regency, South Sulawesi. The research sample consists of 35 eighth-grade students. In collecting data, researchers provided questionnaires or research surveys which were then filled out by students. Based on the results of the data analysis, it was concluded that there is a significant correlation between the use of bulletin board learning media and students' learning outcomes. From the calculation using the independence crostabs test (Contingency Table Analysis), a significance value of 0.02 <0.05 was obtained, which means "There is a relationship between the use of bulletin board media and the level of all indicators of students' learning outcomes in conducting learning".